Transdisciplinary Urbanism and Culture From Pedagogy to Praxis (The Urban Book Series,, 2018)
This book presents a collection of critical, multi-disciplinary essays on urban research by established and early career researchers who participated in the 9th Annual AHRA (Architectural Humanities Research Association) Research Student Symposium. The symposium was held at the Scott Sutherland School of Architecture and Built Environment, Robert Gordon University in Aberdeen from Saturday 19th May to Sunday 20th May 2012. The authors highlight contemporary research issues in urban development in search of new and fresh approaches that reflect the changing principles and praxis of urban conditions. The common ambition is to create new lines of knowledge enquiry in urban research. Due to socio-economic, political and technological changes to urban production and patterns of consumption, as well as a drive for inter-, cross-, multi- and transdisciplinary practice, the essays also reflect the ideological shift currently underway in academic faculties and external research organisations.r‰.